A PROPOSED ARCHIVAL EMPIRICAL RESEARCH METHODOLOGY TO TEST RELIABITIY AND VALIDITY OF DISCOUNTED RESIDUAL INCOME MODEL - Liu, Min Shirley (International Journal of Accounting & Finance Review, 2021)
Kerlinger and Lee (2000) defines reliability as “the proportion of the ‘true’ variance to the total obtained variance of the data yielded by a measuring instrument” and content validity as “representativeness or sampling adequacy of the content—the substance, the matter, the topic of measuring instrument”. The goal of this research is to provide an empirical research method to quantify the reliability and validity of residual income model in the prediction of the value of equity (stock price), by proposing to compare all active U.S. firms from 1981 to 2005 traded in the NYSE and the AMEX (the time period and listed stocks are subject to change based upon the availability of data from different sources). JEL Classification Codes: G10, G17, M41, Z10.